Peningkatan Self Efficacy Remaja Berisiko Menggunakan Terapi Psikoedukasi dengan Musik - Tasman Tasman; Heppi Sasmita; Yessi Fadriyanti; N. Rachmadanur; Lola Felnanda Amri (Jurnal Keperawatan Silampari, 2020)
The purpose of this study was to determine the increase in self-efficacy of adolescents at risk through a combination of psychoeducation therapy with music at SMPN Kota Padang. The research method used in this research is quantitative research with a quasi-experimental research design pre-post test control group. The results showed that the mean score of self-efficacy before the intervention group intervention was lower than the control group. Still, after the intervention was given to adolescents, it showed psychoeducation therapy with music on changes in student self-efficacy at risk. The statistical test results obtained a P value <0.05. In conclusion, there is a significant increase in self-efficacy before and after psychoeducation therapy intervention with music. Keywords: Psychoeducation, Youth, Self Efficacy